Paphlagonia Bölgesi’nde Geç Antik ve Erken Bizans Yerleşimi: Sora / Late Antique and Early Byzantine Settlement in Paphlagonia Region: Sora - Gür, Durmuş; Yıldırım, Yaşar Serkal (Journal of History Culture and Art Research, 2017)
Abstract The late antique, early Byzantine settlement area locates at 12 km. distance to southwest of Karabuk Central District, on a sloping land with an altitude of 700 meters piedmont of Keltepe mountain. This settlement area, called as Zora, Zara, Zopran, Sora, Sopran or some other similar names by the researchers, locates within the boundaries of Akören (Kaleköy) and Zopran today. This area is one of the five central eparchies bounded to Paphlagonia district of Gangra (Çankırı). Various column headers, inscriptions, sculptures, Hellenistic sepulchres and architectural ruins belonging to Roman age are identified there. The settlement area called as Sora since the 4th century is observed by Doublet (1889), Mendel (1901), Gökoğlu (1952), Marek (1993, 2003), Belke (1996) and Umar (2007), and they found out that it used to be called Zobran in the records of 16th century Ottoman archive. Within the scope of this research, Sora is observed in details for the periods of Roman, Byzantine and Ottoman. The life of St. Autonomous, who had came there in the 4th century to proselytize Christianity and became a martyre, their sepulchre constructions, the bishops of the city, architectural plastic works and scriptures are all researched. Moreover, the problem of naming the area which was confusing for many years is tried to be solved by this research beside documenting the present condition of the architectural ruin on their original places. Öz Karabük’ün 12 km. güneybatısında bulunan geç Antik-erken Bizans dönemi yerleşim alanı Sora (günümüzde Zopran ve Akören), Keltepe Dağı’nın eteklerinde ortalama 700 m. rakımda eğimli bir arazi üzerinde yer almaktadır. Araştırmacılar tarafından Zora, Zara, Zopran, Sora, Sopran gibi çeşitli isimlerle adlandırılan yerleşim, günümüzde Akören (Kaleköy) ve Zopran sınırlarında kalmaktadır. Sora, Paphlagonia bölgesinde Gangra (Çankırı) Metropolitliğine bağlı beş Piskoposluk merkezinden biridir. Kentte sütun başlıkları, yazıtlar, heykeller, Hellenistik-Roma dönemine tarihlendirilen mezar odaları ve mimari kalıntılar tespit edilmiştir. Doublet (1889), Mendel (1901), Gökoğlu (1952), Marek (1993, 2003), Belke (1996), Umar (2007) tarafından incelenen, 4.yüzyıldan itibaren Sora olarak adlandırılan yerleşim alanı 16. yüzyıl Osmanlı dönemi arşiv kayıtlarında Zobran olarak geçmektedir. Çalışma kapsamında Sora’nın Roma, Bizans ve Osmanlı dönemi incelenmiştir. Hıristiyanlığı yaymak için 4. yüzyılda Sora’ya gelen ve şehit olan Aziz Autonomous’un hayatı, mezar yapıları, kentin piskoposları, mimari plastik eserleri ve yazıtları incelenmiştir. Çalışmada ayrıca uzun yıllar karıştırılan ve tartışılan yerleşimin adlandırılma sorunu çözümlenmeye çalışılmış, mimari kalıntılar yerinde incelenerek eserlerin günümüz durumları belgelenmiştir.